2018
DOI: 10.5194/acp-2018-378
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effectiveness of Ammonia Reduction on Control of Fine Particle Nitrate

Abstract: Abstract. In some regions, reducing aerosol ammonium nitrate (NH 4 NO 3 ) concentrations may substantially improve air quality. This can be accomplished by reductions in precursor emissions, such as nitrogen oxides (NO x ) to lower nitric acid (HNO 3 ) that partitions to the aerosol, or reductions in ammonia (NH 3 ) to lower particle pH and keep HNO 3 in the gas phase. Using the ISORROPIA-II thermodynamic aerosol model and detailed observational datasets, we explore 25 the sensitivity of aerosol NH 4 NO 3 to … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 57 publications
(80 reference statements)
4
24
0
Order By: Relevance
“…T precursor emissions to one that is sensitive to both NH 3 T and NO 3 T ranges from 2.8 and 3.2, which is in perfect agreement with the analysis of Guo et al (2018). The additional insight that our framework shows is that the "transition pH" varies with temperature and logarithmically with aerosol liquid water content, in response to emissions and diurnal/seasonal variability and climate change.…”
Section: Application Of Frameworksupporting
confidence: 81%
See 1 more Smart Citation
“…T precursor emissions to one that is sensitive to both NH 3 T and NO 3 T ranges from 2.8 and 3.2, which is in perfect agreement with the analysis of Guo et al (2018). The additional insight that our framework shows is that the "transition pH" varies with temperature and logarithmically with aerosol liquid water content, in response to emissions and diurnal/seasonal variability and climate change.…”
Section: Application Of Frameworksupporting
confidence: 81%
“…This sensitivity may be in one direction (e.g., increase of the emissions if the corresponding particulate levels are low and decrease if they are high) or in both. Guo et al (2018) found a "critical" pH of approximately 3, above which the (NO 3 − ) is nearly 1 and almost all nitrate (NO 3 T ) is in the gas phase (HNO3). Here we generalize the approach developing relationships between the terms that depend on aerosol composition, pH and particle 5 water, with temperature still remaining as an independent variable.…”
Section: Determining When Aerosol Mass Is Sensitive To Nitric Acid Anmentioning
confidence: 99%
“…In contrast, more particulate nitrate leads to a slightly higher pH by increasing the particle liquid water and diluting aqueous H + concentrations. Through the comparison of pH predictions among various locations worldwide, Guo et al (2018) also found that a higher particle pH was generally associated with higher concentrations of nitrate. During 2013-2017, the average particle pH varied from 5.0 to 6.2, with a significant decrease in sulfate concentration, resulting in a more neutral atmospheric environment.…”
Section: Influence Of the Transition In Aerosol Characteristics On Pamentioning
confidence: 93%
“…Therefore, a minor reduction in NHx would not be sufficient for air quality improvement. Guo et al (2018) revealed that for winter haze conditions in Beijing, an approximate 60% decrease in NHx was required to achieve an effective reduction in PM2.5. Due to the close linkage between ammonia emissions and agricultural activities, it may be difficult to attain substantial ammonia reduction in China.…”
Section: Influence Of the Transition In Aerosol Characteristics On Pamentioning
confidence: 99%
“…Their findings indicate a large increase of PM2.5 concentrations, the highest of which would occur over the northern Balkan countries (Bulgaria and Romania) and northern Italy. The regulation of agricultural NH 3 emissions has been considered the most effective control strategy for reducing PM2.5 in Europe [28,34,49]. Pozzer et al [56] found that a 50% decrease of NH 3 emissions could reduce the annual, geographical average near-surface PM2.5 concentrations by about 11% across Europe, while with maximum emission controls up to 35% reduction would be possible.…”
Section: Introductionmentioning
confidence: 99%